The Influence of Service Quality, Marketing Mix, on Bank Customer Satisfaction in the Era Covid-19 - Rumiyati Rumiyati; Afriapoll Syafarudin (Ilomata International Journal of Tax and Accounting, 2021)
Building loyalty is no longer an option in the banking world. In recent years a trend has emerged, namely the tendency for customers to have more than one savings account at different banks. One of the ways to do this is by marketing service quality and marketing mix to customer satisfaction. The Bank's compliance with government policies to prevent the spread of COVID-19 is the Work From Home policy. Banking measures to optimize employee efforts to maintain the health of their closest people at home while providing maximum protection from the potential for contracting COVID-19 while interacting with the community while working or traveling to and from the office, namely adjustments to work systems. The role of marketing in banking is to build strong relationships sustainably by providing excellent service for the development of service quality such as Servqual, with Tangible, Responsiveness, Reliability, Assurance, and Empathy characteristics. New service quality that can be applied in the banking world in particular. The most important thing is Banking Service Quality (BSQ.) Like conventional bank service products, the bank's low rating. Testing using the PLS (Partial Least Square) analysis method. The results showed that customer satisfaction has a positive and significant effect on customer loyalty. Customer satisfaction affects the reliability, effectiveness, and assurance of the service portfolio, price, and access. Tangible must receive extra attention so that customer satisfaction can increase.